Profil Darah Dan Kelulushidupan Ikan Nila Pandu F5 (Oreochromis niloticus) yang Diinfeksi Bakteri Streptococcus agalactiae dengan Kepadatan Berbeda - Putri, Rias Ramadhani; Basuki, Fajar; Hastuti, Sri (Journal of Aquaculture Management and Technology, 2013)
Tilapia Pandu (Oreochromis niloticus) is the result repair genetic conducted activities cross breeding between females nila gift and male nila singapore called pandu. This research intent to know and hematology tilapia pandu infected by bacteria Streptococcus agalactiae.Method is used a experimental laboratories. A completely randomized design was applied to the research with 3 treatments and 3 replicates, treatment A (density bactery 105), B (density bactery 107) and C (density bactery 109). Variables tested include the number of erythrocyte, leuchocyte, haemoglobin, hematocrite, blood glucose, and survival rate on days 7 and 14. The results obtained by the infection bacteria S. agalactiae are not significant against hematology and survival rate tilapia pandu. The number of erythrocytes was highest in treatment C for 1.78±0,07x 106 sel/mm3, the highest leucocyte in treatment C for 120,57±4,82 x 103 sel/mm3, the highest haemoglobin in treatment C for 7.70±0.36 g/dL, the highest hematocryte in treatment C for 25.80±1.73%, the highest trombocyte in treatment A for 72,00±61,05 x 103 sel/mm3, the highest blood glucose in the treatment B for 74.53±34,10 g/dL and the highest survival rate in the treatment B and C each for 89.78±0.12%. The results obtained that bacterial infection of S. agalactiae gives no real influence on the blood profile and survival rate tilapia pandu.